Efficacy of different solvent for oleoresin extraction and physicochemical properties of white pepper produced via water retting - Nurul Shahirah Aziz; Noor-Soffalina Sofian-Seng; Wan Aida Wan Mustapha (Penerbit Universiti Kebangsaan Malaysia, 2021)
Initially, four different solvents were compared to determine the best solvent for white pepper oleoresin extraction. Methanol was chosen as it resulted in the highest yield and total phenolic content (TPC) of oleoresin extract from white pepper. This study was also carried out to determine the functional and physicochemical properties of white pepper produced via water retting. Fresh pepper berries were soaked in distilled water (1:2, w/w) at four different temperatures of 28, 35, 42, and 49 ℃ for 16 days. The yield, oleoresin content, colour, fracturability, free radical scavenging activity, and TPC of white pepper produced were determined on the 4th, 8th, 12th, and 16th day of the retting process. Results showed that 8 days of retting at 28 ℃ was sufficient to produce a significantly (p < 0.05) high yield and most fractured white pepper. For other properties, it was suggested that retting time of 8 days was sufficient to produce satisfactory whiteness value, piperine content, free radical scavenging activity, and TPC. Therefore, it can be concluded that the quality of white pepper very much depended on retting temperature compared to the duration of the retting process.